Optimal Hidden Node Area for Enhancing Routing Protocol Performance in IEEE 802.11 Multihop MANETs - Emeka Egbogah; Liqi Shi; Abraham Fapojuwo (Journal of Electrical and Computer Engineering)
The prevalence of hidden node areas in IEEE 802.11 multihop MANETs continues to hinder the performance of routing protocols. This letter presents an analytical model that relates the hidden node area to the hop distance between two communicating nodes. Unlike descriptions from the literature, we describe the hidden node area in terms of multiple layers and the different levels of interference contributed by each layer. We then develop mathematical expressions to determine the probability of successful delivery and end-to-end delay of a packet transmitted over multiple hops to a receiver node exposed to hidden nodes, as a function of hop distance. The numerical results show that decreasing the hop distance increases the probability of successful packet reception at a receiver, at the cost of increased end-to-end delay. However, using a specified delay objective, routing protocols can institute a hop distance threshold metric to limit the number of transmissions that produce collisions in the hidden node area and, thus, maximize their performance.